2014
DOI: 10.1159/000343860
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Epigenetic Profile in Human Hepatocellular Carcinoma and Its Clinical Implications

Abstract: Hepatocellular carcinoma (HCC) is a common cancer worldwide and develops against a background of chronic liver damage. A variety of HCC-related genes are known to be altered by genetic and epigenetic mechanisms. Therefore, information regarding alteration of the genetic and epigenetic profiles in HCC is essential for understanding the biology of this type of tumor. Methylation at CpG sites in gene promoters is known to affect the transcription of the corresponding genes. Abnormal regional hypermethylation is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…It is well known that carcinogenesis is a multistep process involving mutation and subsequent clonal expansion of the mutated cells, and the accumulation of genetic and epigenetic alterations are hallmarks of the cancer genome, including HCC [3,6]. In this study, we tried to clarify alterations in DNA methylation in HCC, one of the characteristics of epigenetic alterations, using the HumanMethylation450 BeadChip array.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that carcinogenesis is a multistep process involving mutation and subsequent clonal expansion of the mutated cells, and the accumulation of genetic and epigenetic alterations are hallmarks of the cancer genome, including HCC [3,6]. In this study, we tried to clarify alterations in DNA methylation in HCC, one of the characteristics of epigenetic alterations, using the HumanMethylation450 BeadChip array.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that hepatocarcinogenesis involves multiple molecular pathways with the accumulation of genetic and epigenetic alterations, including point mutations and abnormal DNA methylation [3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…In the liver, the hypermethylation of CpG-10.11 (14,15), CpG-21 and the hypomethylation of CpG-12 in Msh2, which were all uniquely detected in non-tumor groups, may be associated with tumor-free status following MNU induction. Similarly, in the kidney, the hypermethylation of CpG-5, CpG-20 may be associated with tumor-free status following MNU induction.…”
Section: Discussionmentioning
confidence: 95%
“…DNA methylation is the best-known epigenetic modification, and aberrant methylation in the promoter region 5'-C-phosphate-G-3' (CpG) islands is associated with gene silencing, as this downregulates transcription (12,13). In human types of cancer, altered methylation patterns epigenetically repress tumor suppressor genes, providing a direct link between epigenetic regulation and cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent technical advancement in genomic sequencing and comprehensive methylation analyses give us a profound insight into the molecular events that drive carcinogenesis, including HCC [3,4,5,6,7,8]. Several studies have noted abnormal DNA methylation in HCC; DNA methylation of specific sequences on the promoters of tumor suppressor genes (TSGs) is a key epigenetic alteration that marks HCC pathogenesis [2,9].…”
Section: Introductionmentioning
confidence: 99%